A study of learners' perceptions of online intercultural exchange through Web 2.0 technologies. Issue 3 (19th March 2014) - Lee, Lina; Markey, Alfred
Abstract This paper reports a Spanish-American telecollaborative project through which students used Twitter, blogs and podcasts for intercultural exchange over the course of one semester. The paper outlines the methodology for the project including pedagogical objectives, task design, selection of web tools and implementation. Using qualitative and quantitative data collection, the study explored how the application of Web 2.0 facilitated cross-cultural communication. How the use of digital technology affected the way in which the students viewed intercultural learning and peer feedback was examined. The findings showed that students viewed the online exchange as a superb venue for intercultural communication with native speakers. Through social engagements, students not only gained cultural knowledge but also became more aware of their own beliefs and attitudes toward their own culture. In addition, discussions on topics of tangible and intangible cultures afforded the opportunity to raise students' awareness of cultural norms and practices. Peer feedback helped learners increase lexical knowledge, prevent language fossilization, and acquire native-sounding discourse. The study suggests that allocating sufficient time to complete each task and making personal commitment to online contributions are essential to successful intercultural exchanges.